Serum Free Light Chains in Common Variable Immunodeficiency Disorders: Role in Differential Diagnosis and Association With Clinical Phenotype - Scarpa, Riccardo; Pulvirenti, Federica; Pecoraro, Antonio; Vultaggio, Alessandra; Marasco, Carolina; Ria, Roberto; Altinier, Sara; Compagno, Nicolò; Firinu, Davide; Plebani, Mario; De Carli, Marco; Matucci, Andrea; et al. (Frontiers in Immunology, 2020)
We report on an observational, multicenter study on 345 adult CVID patients, designed to to assess the diagnostic value and the clinical correlations of serum free light chains (sFLC) pattern in Common Variable Immunodeficiency disorders (CVID). As control groups we included 138 patients affected by undefined primary antibody defects (uPAD), lymphoproliferative diseases (LPDs) and secondary antibody deficiencies not related to hematological malignancies (SID). CVID patients presented lower κ and λ chains concentration compared to controls. On the basis of sFLC pattern, patients were classified into 4 groups: κ−λ+, κ+λ−, κ−λ−, κ+λ+. The most common pattern in CVID patients was k-λ- (51%), followed by k-λ+ (25%), k+λ+ (22%), and k+λ- (3%). In uPAD, LPDs and SID groups κ+λ+ was the most common pattern observed. By analyzing correlations between sFLC patterns and disease-related complications of CVID, we observed that κ-λ+ subjects more frequently presented an “infection only” phenotype; κ+λ+ patients were more prone to autoimmune cytopenia and lymphoproliferative phenotype; on the other hand, patients belonging to the κ-λ- group presented more commonly unexplained enteropathy and showed higher frequency of bronchiectasis and splenomegaly compared to κ-λ+ patients. When compared to the other groups, κ-λ- had also lower serum IgG, IgA and IgM concentration at diagnosis, lower frequency of CD27+IgD-IgM- Switched Memory B and higher frequency of CD21low B cells, receiving earlier CVID diagnosis. Thus, lower levels of sFLC might be an epiphenomenon of an impairment in B cell differentiation, possibly leading κ-λ- patients to a higher risk for bacterial infections and chronic lung damage. Based on these results, we suggest adding sFLC assay to the diagnostic work-up of hypogammaglobulinemia and during follow-up. The assay may be useful to differentiate CVID from other causes of hypogammaglobulinemia and to early detect monoclonal lymphoproliferation occurring over years. Moreover, since sFLC pattern seems to be related to disease phenotypes and clinical manifestations of CVID and after confirmation by further studies, sFLC assay might be considered a promising prognostic tool for identifying patients at higher risk of developing enteropathy and chronic lung damage or lymphoproliferation and autoimmune cytopenia. This will allow designing a tailored follow-up for CVID patients.